Effect of row ratios and organic nutrient management on productivity and economics of Indian mustard (Brassica juncea) + chickpea (Cicer arietinum) intercropping system - TRIPATHY, SASMITA; MEENA, S L; DHAR, SHIVA; PAUL, SANGEETA; SINGH, SACHIN (The Indian Journal of Agricultural Sciences, 2023)
A field experiment was conducted during winter (rabi) seasons of 2021–22 and 2022–23 at the research farm of Indian Agricultural Research Institute, New Delhi to find out the suitable cropping system with optimum row ratio and nutrient management practice in Indian mustard [Brassica juncea (L.) Czern.] + chickpea (Cicer arietinum L.) intercropping system. Cropping systems i.e. mustard sole; chickpea sole; mustard + chickpea 2:5; mustard + chickpea 5:2 was taken as main plots. Nutrient management practices i.e. control; 60 kg Nitrogen/ha; 20 kg Nitrogen through farmyard manure + leaf manure; 20 kg Nitrogen through farmyard manure + leaf manure + microbial consortia were taken as sub-plots to attain a higher degree of precision. It was observed that though the crop yields of individual crops of mustard and chickpea were the highest in sole crop, but yield of intercropping system in terms of mustard equivalent yield was found to be the highest for mustard + chickpea 5:2 row ratio. Yields of both mustard and chickpea were observed to be the highest in the plots treated with combination of organic manures and microbial consortia i.e. 20 kg nitrogen through farmyard manure + leaf manure @4 t/ha + microbial consortia. Highest gross returns, net returns and benefit-cost ratio were found in mustard + chickpea 5:2 row ratio. Analysis of intercropping indices revealed the highest intercropping advantage in mustard + chickpea 5:2 row ratio when treated with organic manures and microbial consortia. Intercropping systems had land equivalent ratio more than unity, depicting advantage. Aggressivity values showed mustard crop was dominant over chickpea.